Prevalence of Myopia and Its Association with Indoor and Outdoor Sport Participation among University Student Athletes in Thailand - Naksaranyuyottana, Phongvarin; Watanathawornwong, Kritchai; Jenchitr, Watanee; Pokaisasawan, Akachai (Journal of Current Science and Technology, 2026)
Myopia is a growing public health problem in East and Southeast Asia, but evidence among university athletes remains limited. This cross-sectional study determined the prevalence of myopia among amateur university athletes at Rangsit University, Thailand, and examined associations with sport environment and selected risk factors. A total of 157 athletes (115 males, 42 females; mean age 19.79 ± 1.88 years) completed a demographic questionnaire and underwent axial length measurement, slit-lamp biomicroscopy, non-mydriatic fundus photography, autorefraction, and manifest refraction. Myopia was defined as a spherical equivalent ≤ −0.50 D using the more myopic eye. Sports were classified as indoor or outdoor according to the primary training and competition environment. Multivariable logistic regression was used to assess associations with family history of myopia, sport environment, sleep duration, years of athletic practice, daily training duration, and gender. Overall myopia prevalence was 51.60% (81/157). A positive family history was associated with higher odds of myopia (AOR = 2.53; 95% CI: 1.25–5.12; p = 0.010). After adjustment, indoor sport participation was associated with higher odds compared with outdoor sport participation (AOR = 2.44; 95% CI: 1.14–5.23; p = 0.021). Sleeping >6 hours per day was protective (AOR = 0.37; 95% CI: 0.18–0.79; p = 0.010). Gender, years of practice, and daily training duration were not significant predictors. These findings suggest that regular sports participation alone may not offset myopia risk when training occurs mainly indoors. Vision screening for student-athletes should consider family history, sport environment, and sleep habits.